Tuberkulosis Paru Anak dengan Hemoptisis dan Resistensi Rifampisin Indeterminate: Laporan Kasus - Imtinan Khoirunnisa; Shinta Nareswari (Medula, 2026)
Tuberculosis (TB) in children remains a major contributor to global morbidity and mortality. Although clinical manifestations such as hemoptysis have been increasingly reported in adolescents, the primary diagnostic challenge in this case lies in the Molecular Rapid Test (TCM) GeneXpert result showing indeterminate rifampicin resistance. The patient's chest X-ray showed primary pulmonary TB, consistent with positive Mantoux and lipoarabinomannan (LAM) TB test results. TCM GeneXpert examination confirmed pulmonary TB bacteriologically, with MTB trace detected and indeterminate rifampicin resistance. In addition, Gram staining of sputum showed a mixed flora of bacteria and fungi, reflecting colonization or potential infection in the respiratory tract. The patient was diagnosed with bacteriologically confirmed pulmonary TB with hemoptysis and anemia due to chronic disease, and was well-nourished. Medical interventions included a first-line Anti-Tuberculosis Drug (OAT) regimen and symptomatic therapy. The patient's clinical outcome was excellent, characterized by the immediate cessation of hemoptysis post-tranexamic acid initiation and the achievement of overall clinical improvement during hospitalization.  Overall, indeterminate rifampicin in TCM with a low (trace) bacterial load requires thorough clinical correlation to guide timely therapy.